A Study of Vibration and Wear Resistance of Friction Stir Processed Metal Matrix Composite. (2018) - Sharma, Harsh; Kumar, Kaushal; Kumar, Rajeev; Gulati, Piyush
Abstract: Fabrication of mono, hybrid and nanocomposites is becoming an emerging field nowadays. The fabricated MMCs are used in the manufacturing of aircraft, aerospace, and aeronautics due to their better mechanical and tribological properties in comparison with the traditional fiber-reinforced composites. For fabricating metal matrix composites, friction stir processing is an evolving technique. In this study, the effect of vibrations on the properties of friction stir processed alloy is reviewed. A literature review related to the wear resistance analysis of friction stir resistance analysis of friction stir processed metal matrix composite is presented.